1994
DOI: 10.1002/1098-108x(199401)15:1<21::aid-eat2260150104>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Excessive physical activity in dieting disorder patients: Proposals for a supervised exercise program

Abstract: A relationship between starvation and hyperactivity has been observed in animal models, in experiments with human subjects, and in dieting disorder patients. Since the earliest descriptions of anorexia nervosa, excessive physical activity has figured prominently as a symptom of the illness, yet little attention has been directed towards this phenomenon. The aims of this paper are to review the published literature, to report our experience of the role of physical over activity in the clinical presentation of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
124
0
24

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(153 citation statements)
references
References 34 publications
5
124
0
24
Order By: Relevance
“…However, work based on body assessment and specific bodily concerns in the context of anorexia nervosa is sparse (Fisher and Schenkman, 2012;Hechler et al, 2005). Nevertheless, changing the way in which patients with anorexia nervosa experience their bodies is assumed to be an important indication for physiotherapy, and interventions aimed at modifying body awareness and bodily experiences have been proposed (Vandereycken et al, 1987;Beumont et al, 1994;Probst et al, 2013;Probst et al, 1995). One paper has discussed the potential of body awareness therapies in terms of increasing body contact, initiating novel ways of sensing and interpreting bodily signals, as well as improving emotional awareness through the body (Kolnes, 2012).…”
Section: Physical Therapy Interventionsmentioning
confidence: 96%
“…However, work based on body assessment and specific bodily concerns in the context of anorexia nervosa is sparse (Fisher and Schenkman, 2012;Hechler et al, 2005). Nevertheless, changing the way in which patients with anorexia nervosa experience their bodies is assumed to be an important indication for physiotherapy, and interventions aimed at modifying body awareness and bodily experiences have been proposed (Vandereycken et al, 1987;Beumont et al, 1994;Probst et al, 2013;Probst et al, 1995). One paper has discussed the potential of body awareness therapies in terms of increasing body contact, initiating novel ways of sensing and interpreting bodily signals, as well as improving emotional awareness through the body (Kolnes, 2012).…”
Section: Physical Therapy Interventionsmentioning
confidence: 96%
“…Calogero and Pedrotty 17 found reduction in exercise compulsivity and dependence among patients who attended a supervised PA program during treatment of ED. This supports the perspective of Beumont et al, 20 who proposed to use supervised PA as a strategy in the management of excessive PA and exercise dependence.…”
Section: Introductionmentioning
confidence: 99%
“…Dopaminergic neuronal function modulates feeding behavior (Szczypka et al, 1999(Szczypka et al, , 2000, motor activity (Kalivas, 1993), and rewardmotivated (Blum et al, 1995;Salamone, 1996) and drugseeking behavior (Bardo et al, 1996). Aside from their wellknow disturbances of feeding and weight maintenance, individuals with AN have stereotypic and hyperactive motor behavior (Kron et al, 1978;Beumont et al, 1994), anhedonic, obsessional personalities, and reduced novelty seeking (Sohlberg and Strober, 1994). Moreover, we have shown that individuals who have recovered from AN exhibit significantly lower CSF homovanillic acid concentrations than individuals with a history of BN diagnosis or control individuals (Kaye et al, 1999).…”
Section: Introductionmentioning
confidence: 99%